The problem of children’s right to participation in early childhood education and care - Skrzypczak, Marta (Society Register, 2022)
Participation, a highly debated topic, is understood as a right to self-determination and a right to be involved in the decision-making in matters that concern one’s life. Also, in the field of Early Childhood Education and Care (ECEC) in Germany, children’s participation plays an important role, embedded in the legislation. However, research shows that children still do not participate in decisions in their daily life in childcare facilities. This problem has been linked to the negative attitudes of early childhood educators, their fear of losing control, sharing power with children, or even lack of knowledge. The recent qualitative case study, examining educators’ participation perspectives by applying semi-structured interviews and a focus group, demonstrated that educators understand what participation means differently and view it as a concept rather than a right. However, they perceive it as having enormous importance and are keen to embrace it. Their attitudes depend significantly on their experiences and the behavioural scripts they internalized. Another factor influencing children’s participation is the organizational culture of a childcare facility. It is correlated with the quality of care in childcare settings. To this end, studying and ensuring positive work relationships proves to be necessary. Applying collaborative leadership and democratic, participatory structures is essential to children and adults alike. A genuinely respectful environment designed to promote self-determination, deep reflection, ongoing training, and support are key in realizing children’s right to participation in ECEC.